The oxidation reaction of quinine by potassium permanganate (KMnO4) - Rosalina, Reny; Alni, Anita; Mujahidin, Didin; Santoso, Joko (Research Institute for Tea and Cinchona, 2015)
Quinine was known widely as malarial drug and a bitter taste ini soft drink. Recently, quinine have been also applied in organo-catalysis process, separation and purification of chiral compounds from enantiomeric mixture by diasteromeric salt crystallization and chiral chromatography. Quinine contains various functional groups which easily transforms by oxidations. This research was to study the oxi-dation reaction of quinine by using potassium permanganate (KMnO4) as oxidator. The KMnO4 oxidation carried out under acidic con-ditions. The separation and purification of pro-ducts were done by radial chromatography with chloroform : metanol : tri ethyl amine (9:1:0.1) as eluent. The structure of products were cha-racterized by spectroscopic data including: in-frared spectroscopy, NMR, and mass spectro-metry as quinine-1-N-oxide and quininal.